Home care nurses' identification of patients at risk of infection and their risk mitigation strategies: A qualitative interview study. (July 2020) - Dowding, Dawn; Russell, David; Trifilio, Marygrace; McDonald, Margaret V.; Shang, Jingjing
Abstract: Background: There is an increase in the number of individuals who receive care at home. A significant proportion of these patients acquire infections during their care episode. Whilst there has been significant focus on strategies for infection prevention and control in acute care environments, there is a lack of research into infection prevention in a home care setting. Objectives: To understand (1) if and how home care nurses identify patients at high risk of infection and (2) the strategies they use to mitigate that risk. Design: A qualitative descriptive study, using semi-structured interviews. Setting: A large not for profit home care agency located in the New York region of the United States. Participants: Fifty nurses with a range of experience in home care nursing. Methods: Purposive and snowball sampling was used to recruit nurses from across the home care agency with varied years of work experience. Interviews were audio recorded and transcribed. The interviews explored how home care nurses evaluate their patients' risk of developing an infection and if/how they modify the plan of care based on that risk. Data were analysed using thematic analysis. Results: Three themes were derived from the data; assessing a patient's risk of infection, the risk assessment process, and strategies for mitigating infection risk. Factors identified by nurses as putting a patient at higher risk of infection included being older, having diabetes, inadequate nutrition; along with inadequate clinical information available at start of care. The patient's knowledge and understanding of infection prevention, and the availability and knowledge of caregivers were also important, as was the cleanliness of the home environment. Given the context of home care, where nurses have little control over the environment and care processes in-between visits, the main strategy for infection prevention was patient and caregiver education. Nurses also discussed the importance of their own infection prevention behaviours, and the ability to adjust a patient's plan of care according to their infection risk. Conclusions: The study highlights the complexity of the risk assessment process in relation to infection. Existing guidelines for infection prevention and control do not adequately cover the home care environment and more research needs to determine which interventions (such as patient/caregiver education) would be most effective to prevent infections in the home care setting.